Dosimetric Study on Natural Background Ionizing Radiation and Impact Assessment on Public Health: A systematic Review in Nigeria - Buhari Samaila; Yaseer Musa Sagagi; A. Bello; Sadiq Muhammad; A. M Imam; I. I Garba; H. Isah; R. Muhammad (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Environmental natural background ionizing radiation contamination and degradation is a global concern because of its negative effect on public health. Public health risk continues to be one of the environmental and public concerns in Nigeria. The emission of natural background ionizing radiation from the outer space, crust of the earth, food, and water and construction materials contributed a lot to the public environmental exposure. The populations’ exposure to background radiation emanated from terrestrial, cosmic, and internal radiation account for 82% which are out of control. Present work was aimed to carry out an investigational study of the natural background ionizing radiation levels, identify locations with high or low BIR and assess the health effect within Nigeria’s communities based on the available data extracted from the literatures and establish a baseline data of exposure rate, absorbed dose rate, annual effective dose equivalent, and excess life cancer risk from outdoor and indoor background radiation. This dosimetric study of natural background radiation in Nigeria is important to monitor the levels of radiation to which people are exposed directly or indirectly. Recently, several studies have been done in Nigeria and different values were reported based on indoor and outdoor background radiation doses. In this paper, a review and literature survey of natural background ionizing radiation was carried out. The data extracted based on indoor and outdoor revealed that Plateau, Oyo, River, Delta and Ondo, Sokoto, Kano and Niger have the highest value of dose rate compared to the world average value. The order of magnitude of the dose rate were Plateau > Oyo > Rive > Delta > Ondo and River > Plateau > Sokoto > Kano > Oyo > Ondo > Delta > Niger for Indoor and outdoor respectively. The highest outdoor & indoor annual effective doses were observed in OYO, Sokoto, Ondo, Delta, Akwanga, Plateau, and River. The results were comparatively greater than the world acceptable limit of 1.0 mSv/y. The order of magnitude of annual effective are OYO > Sokoto > Ondo > Niger Delta and Akwanga > Plateau > Delta > River for outdoor and indoor respectively. The regions with highest excess life cancer risks in Nigeria were observed in Oyo, Akwanga, Ondo, Plateau, River, Kaduna, Anambra, Port court, Abuja, Delta, Ibadan and Kano. Radiation cancer induction values obtained were remarkably high compared to world average value of 0.29×10-3. The amount of radiation absorbed by individual organs exposed to high natural background radiation areas were observed to be highest in tests organ, the order of magnitude were Tests > Bone marrow > Whole body > Lung > Ovaries > Kidney > Liver. But all the estimated mean values of organs doses were remarkably lower than that of world average value. Since the mean absorbed dose rate and annual effective dose in several areas is higher than 0.084µSv/h and 1.0 mSv/year for general public in many locations, long term exposure of the public to these radiations may lead to radiation induced health hazard such as erythema, skin cancer, genetic mutation and sterility.